(untitled) (Proceedings OPTIMAL, 2024)
When pregnancy occurs, there are several changes, including physiological changes and psychological changes. These changes occur due to the presence of the hormone estrogen and progesterone during pregnancy. One of the effects of physiological changes includes leg cramps, this condition causes discomfort and if left unchecked has further impacts such as disrupting the mother’s rest pattern as a result of leg cramps. The aim of this care is to carry out midwifery care during pregnancy appropriately, so that any discomfort that arises can be resolved. The research method used is descriptive research and uses a case stufy approach and research studies using Midwifery Care and documented in the form of SOAP (Subjective, Objective, Analysis, Management). The care provided is in the form of education about the various discomforts of the third trimester and how to deal with leg cramps.